Developing conductive immiscible polystyrene/polypropylene blends with a percolated conducting polyaniline/polyamide filler by tuning its specific interactions with the styrene‐based triblock compatibilizer grafted with maleic anhydride. Issue 9 (31st August 2019) - Bharati, Avanish; Hejmady, Prakhyat; Van der Donck, Tom; Seo, Jin Won; Cardinaels, Ruth; Moldenaers, Paula
ABSTRACT: An approach to induce conductivity in immiscible polystyrene/polypropylene (PS/PP) blends is described using a percolated conducting polyaniline/polyamide (PANI/PA) filler combined with a polystyrene‐block‐poly(ethylene‐ran‐butylene)‐block‐polystyrene‐graft‐maleic anhydride compatibilizer. The approach is based on the ability of the compatibilizer to concomitantly stabilize the cocontinuous morphology and to improve the state of dispersion of the PANI/PA filler. Selective localization of PANI/PA in the PS phase with improved filler dispersion is achieved with the optimal master batch (MB) preparation technique followed by its optimized sequence addition to the blend components. This results in an increase in the dc conductivity by six decades as compared with that of the neat compatibilized blend at an effective 4.8‐wt % PANI concentration. An investigation of the effect of functionality and concentration of the filler and the compatibilizer on the filler connectivity in the blend is performed. The prevailing specific interactions are analyzed by Fourier transform infrared spectroscopy and thermogravimetric analysis of the MBs. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48433. Abstract :